Association between environmental exposure to benzene and oxidative damage to nucleic acids in children / Associazione tra esposizione ambientale a benzene e danno ossidativo al DNA nei bambini - Andreoli, Roberta; Protano, Carmela; Manini, Paola; De Palma, Giuseppe; Goldoni, Matteo; Petyx, Marta; Rondinone, Bruna Maria; Vitali, Matteo; Mutti, Antonio (La Medicina del Lavoro, 2012)
SummaryObjectives: To evaluate the association between environmental exposure to benzene and oxidative damage to nucleic acids in children, also considering the role of Environmental Tobacco Smoke (ETS). Methods: 396 children living in central Italy were recruited in districts with different urbanization and air pollution. All biomarkers were determined in spot urine samples by mass spectrometric techniques to assess exposure [benzene (U-Benz), and its metabolites (t,t-muconic and S-phenylmercapturic acids, t,t-MA and S-PMA, respectively), cotinine] and nucleic acid oxidation [8-oxo-7,8-dihydro-2’-deoxyguanosine (8-oxodGuo), 8-oxo-7,8-dihydroguanosine (8-oxoGuo), and 8-oxo-7,8-dihydroguanine (8-oxoGua)]. Results: Biomarkers of exposure and nucleic acid oxidation increased with urbanization and were correlated with each other (r>0.18, p